The study results of winter wheat varieties in the Sverdlov region - G. N. Potapova; N. L. Zobnina (Зерновое хозяйство России)
Winter soft wheat is a promising crop for growing in the Middle Urals. At present its cultivation is constantly increasing in the agricultural farms of the Sverdlov region. The amount of sowing areas ranges from 1.5 to 3 thousand hectares. The average productivity of winter wheat of the Sverdlov region was 1.45-2.21 t/ha during the last years. According to the productivity wheat yields coincided or slightly exceeded the productivity of winter rye. The range of varieties tolerant to unfavourable winter conditions of the Middle Urals is increasing. Among the varieties tested on the variety plots of 2014 and 2015 the cultivars ‘Bis’, ‘Italmas’ and ‘Poema’ showed the best winter resistance. They produced larger yields than the standard variety ‘Volzhskaya K’. The average productivity of the varieties during last three years was the largest one on the Bogdanovich variety test plot (5.1 t/ha). In the tests of Ural RIA there have been selected the varieties ‘Volzhskaya 3’, ‘Kazanskaya 560’, ‘Moskovskaya 59’ and ‘Albina’, which produce high yields of grain and possess high indexes of adaptive ability. The variety ‘Volzhskaya 3’ possesses the highest indexes of general adaptive ability (Vi =0,41) and stability (σ2 =4.8 + Sgi =52.0), but a low level of plasticity (bi=1,13). The variety ‘Kazanskaya 560’ possesses a high level of plasticity (bi=1.0) and the largest breeding value of a genotype (СЦГi=13.91). The variety ‘Moskovskaya 59’ has got a high level of plasticity (bi=1.03) and a large breeding value of a genotype (СЦГi=11.8). It has been determined that a careful choice of varieties with a compliance with cultivation technology will allow obtaining positive results if increase sowing areas for winter soft wheat on the Middle Urals.